Distribution of trespass cannabis cultivation and its risk to sensitive forest predators in California and Southern Oregon. - Greta M Wengert (Public Library of Science (PLoS), 2021)
Illegal cannabis cultivation on public lands has emerged as a major threat to wildlife in California and southern Oregon due to the rampant use of pesticides, habitat destruction, and water diversions associated with trespass grow sites. The spatial distribution of cultivation sites, and the factors influencing where they are placed, remain largely unknown due to covert siting practices and limited surveillance funding. We obtained cannabis grow-site locality data from law enforcement agencies and used them to model the potential distribution of cultivation sites in forested regions of California and southern Oregon using maximum entropy (MaxEnt) methods. We mapped the likely distribution of trespass cannabis cultivation sites and identified environmental variables influencing where growers establish their plots to better understand the cumulative impacts of trespass cannabis cultivation on wildlife. We overlaid the resulting grow-site risk maps with habitat distribution maps for three forest species of conservation concern: Pacific fisher (Pekania pennanti), Humboldt marten (Martes caurina humboldtensis), and northern spotted owl (Strix occidentalis caurina). Results indicate that cannabis cultivation is fairly predictably distributed on public lands in low to mid-elevation (~800-1600m) forests and on moderate slopes (~30-60%). Somewhat paradoxically, results also suggest that growers either preferred sites inside of recently disturbed vegetation (especially those burned 8-12 years prior to cultivation) or well outside (>500m) of recent disturbance, perhaps indicating avoidance of open edges. We ground-truthed the model by surveying randomly selected stream courses for cultivation site presence in subsets of the modeling region and found previously undiscovered sites mostly within areas with predicted high likelihood of grow-site occurrence. Moderate to high-likelihood areas of trespass cultivation overlapped with 40 to 48% of modeled habitats of the three sensitive species. For the endangered southern Sierra Nevada fisher population, moderate-high likelihood growing areas overlapped with over 37% of modeled fisher denning habitat and with 100% of annual female fisher home ranges (mean overlap = 48.0% + 27.0 SD; n = 134) in two intensively studied populations on the Sierra National Forest. Locating and reclaiming contaminated cannabis grow sites by removing all environmental contaminants should be a high priority for resource managers.